Methodological principle of interdisciplinarity in the history of economics - Лісовицький, В. М. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
Throughout its history, economic science has been influenced by the principles and methods of more exact sciences. This influence can be traced in the concepts of both classical and neoclassical schools. The latter interpreted economic phenomena and processes from a subjective psychological point of view and contributed to the formation of a particular scientific direction – economic psychology. Institutional school that views the economy as an evolving system has generated such an interdisciplinary trend as economic genetics. The influence of exact sciences on the economic thought has manifested itself not only in the wide application of mathematical modeling, but also in the reference to the analogy with physical processes which formed another interdisciplinary research field – econophysics. Experiencing the influence and employing research methods of natural and exact sciences, economic science in turn ‘penetrates into the territory’ of social disciplines (sociology, politology, history) which generated separate directions of economic analysis: home economics, public choice theory, economic history etc. Such an approach which has not always been favourably received by the experts in related disciplines has been named «economic imperialism» whose representatives are supporters of both neoclassic and new institutional theory. Methodological mainstream is being replaced by methodological pluralism which would entail the coexistence of different theoretical perspectives and interdisciplinary approach is an essential element in building this tradition. This places new demands on the quality of economic education. A modern economist must have knowledge in different sciences and be able to use their analytic apparatus. At the post-nonclassical stage in its development the science of economics makes extensive use of interdisciplinary principles and analytical tools of both natural and humanitarian sciences, having achieved notable progress along this path. Interdisciplinary linkages allow us to reveal deeper patterns, bring to a qualitatively new level of scientific knowledge. Although interdisciplinarity do not always demonstrate effective results it may be considered as one of perspective means of solving complex problems of modern times.